Efektivitas Media Lilin Aromaterapi Berbahan Daun Pala (Myristica fragrans Houtt) dalam Mematikan Nyamuk Aedes aegypti - Sitti Washliyah; Mariyana Ismail (Universitas Sam Ratulangi, 2023)
Dengue fever is transmitted through the bite of a female mosquito that stores the dengue virus in its eggs, then the virus will be transmitted to humans through bites. The right way to control the spread of Dengue Fever is to control the vector population through the use of bioinsecticides whose basic ingredients come from plants containing chemicals that are toxic to insects. This study aims to determine the effectiveness of aromatherapy candle media made from nutmeg leaf (Myristica fragrans houtt) in killing the Aedes aegypti mosquito. This research uses experimental research with post test only group control design method. The number of samples used in one experiment was 50 Aedes aegypti mosquitoes. This research process uses palm wax wax media, and the composition of nutmeg leaf powder is 50 grams and wax is 100 grams. The results showed that for 12 hours every 2 hours the number of dead mosquitoes was monitored, the average number of mosquitoes that died with 3 trials was 60% experiment, while external factors, namely temperature and humidity measurements in both rooms did not affect the mortality of mosquitoes.